Efficacy of three isolates of Trichoderma harzianum Rifai against major fungal pathogens of tomato - ABHAY K. PANDEY*, S.K. SAIN and (Indian Phytopathology, 2016)
In the present study 3 isolates of Trichoderma harzianum were evaluated against six pathogens viz., Fusarium, Pythium, Phytophthora, Rhizoctonia, Alternaria and Septoria species causing diseases in tomato. All the isolates of T. harzianum inhibited radial growth of all six fungal pathogens and isolate Th-sks was found to be most effective antagonist with 68-79.47% range of percent mycelia inhibition. Volatile compounds of Th-Ke isolate were more effective in inhibition of S. lycopersici and A. alternata growth and Th-Sks against P. aphanidermatum and P. infestans. Non-volatile metabolites of isolate Th-Sks exhibited 100% inhibition of S. lycopersici, 55.6% inhibition of A. alternata, 64.6% of R. solani, 45.3% of P. aphanidermatum and 42.1% of P. infastans. Thus, it is concluded that isolate Th-Sks can be used as a biocontrol agent for management of fungal pathogens of tomato.